Down-regulation of colon mucin production induced by Eimeria pragensis infection in mice - Setia, Yulia Dwi; Kokubo-Tanaka, Mio; Tanaka, Ryusei; Yoshida, Akemi; Nagayasu, Eiji; Ahmadi, Parnian; Yoshida, Ayako; Maruyama, Haruhiko (Frontiers in Parasitology, 2025)
IntroductionEimeria pragensis, an intestinal protozoa infecting mice, induces colitis and reduces goblet cell numbers in the large intestine. In the present study, we investigated the pathogenesis and the mechanisms underlying goblet cell down-regulation in the early phase of infection.MethodsMale C57BL/6 mice were orally infected with 300 oocysts. Fecal oocyst shedding and body weight were monitored daily. Colon tissues were collected at 3, 8, and 13 days post-infection (dpi) to assess pathological changes. Parasite burden was assessed by histological analysis (H&E staining) and qPCR targeting 5S rRNA. Goblet cells were visualized using PAS-Alcian Blue staining and Muc2 immunohistochemistry. To elucidate mechanisms of goblet cell dysfunction, we performed RNA sequencing of large intestine tissue to examine host as well as parasite transcriptomes.ResultsFecal oocyst excretion peaked at 8–9 dpi. Body weight decreased from 6 to 11 dpi, with recovery after 12 dpi. Maximal parasite accumulation in the proximal colon was observed at 8 dpi in histological examination as well as qPCR. Colon length was significantly shortened at 3 dpi. Goblet cell area significantly reduced at 8 dpi (p < 0.05). RNA sequencing of infected large intestines revealed that E. pragensis produced enzymes that were known to degrade mucin and tight junctions, and proteins that could activate the Notch–Hes1 signaling pathway. As for host responses, genes associated with Th1-type inflammation, epithelial barrier disruption, and immune regulation were up-regulated as early as 3 dpi.DiscussionOur findings suggested that E. pragensis infection induces a mucosal barrier dysfunction in the early phase of the infection, which possibly causes the tissue invasion of bacteria in the large intestine. Th1-type inflammatory response, thus induced, reduces goblet cell numbers and mucin production. This model provides valuable insight into the mechanisms of mucosal barrier disruption during protozoan infection.